The use of WEB-oriented technologies in the process of WEB-programming teaching for technical universities students (Educational Dimension, 2025)
The realities of the XXI century - informatization, digital transformation, high technologies, WEB-technologies in particular - put Ukraine state in front of global challenges of creating a digital state. It is the implementation of a number of digital projects which form the digital space of the state, in particular those coordinated by the Ministry of Digital Transformation of Ukraine. The development of a significant number of applications requires the state to constantly update them, maintain them working, which requires qualified programmers. The task of technical universities is to train competitive specialists in the IT field. This study analyzes the results of a survey of students of NTUU "Kyiv Polytechnic Institute. Igor Sikorsky ”, the purpose of which was to find out what integrated development environments and programming languages ​​senior students independently choose when developing programs within the educational and professional programs of the faculty, and which correlate with software used by programmers in the implementation of large IT-enterprises, in particular WEB-programming languages. The results of the study showed as well that the rating of programming languages and the use of integrated development environments meet modern requirements for software development. 76.7% of graduates, while being students, are already employed in IT companies as full-time employees. The high percentage of employment suggests that graduate students of the Faculty of Informatics and Computer Engineering of Igor Sikorsky NTUU KPI are competitive in the modern IT labor market.
Keywords: programming language; integrated development environment; IT graduates competitiveness